Waking the Community for Sahur: Ramadan Heritage, Social Solidarity, and Cultural Transformation in Indonesia - M. Nasihudin Ali; Rani Lestari; Ade Idra Suhara (Center for Research and Development of Religious Literature and Heritage, 2026)
The tradition of waking the community for sahur is a cultural practice in Ramadan that continues to be observed across many regions of Indonesia, taking diverse local forms such as ronda sahur in Java, sahur bagarak in South Kalimantan, arakan sahur in Jambi, and keliling sahur in Langkat. This study examines how the sahur wake-up tradition has changed in form, function, and meaning under conditions of modernization. It uses a qualitative literature-based method in which data drawn from journal articles, academic books, and other relevant publications were analyzed through an interpretive cultural approach to trace the relationship between religious practice, local culture, and social change. The findings show that the tradition originally served as a communal means of signaling the time of sahur using kentongan, bedug, rebana, and other traditional instruments. As this practical function has been displaced by modern technology, the tradition has not disappeared but has been reconstituted as a more symbolic cultural practice, expressed through sahur festivals, Ramadan cultural processions, community art performances, and digital documentation on social media. This transformation indicates that the tradition now functions less as a practical reminder than as a vehicle for cultural identity and social solidarity among Muslim communities. The article contributes to the study of intangible cultural heritage by showing that the sahur wake-up tradition is not merely preserved but actively reconstructed through a heritage-making process, in which community participation, youth transmission, Ramadan soundscapes, festivalization, spatial negotiation, and digital documentation jointly convert a practical religious custom into a dynamic form of Ramadan cultural heritage. The study concludes that this tradition constitutes a form of intangible cultural heritage capable of adapting to social and technological change without losing the values of togetherness, religiosity, and cultural identity that sustain it.